Pengaruh Manajemen Mutu Total dan Komunikasi Terapeutik Terhadap Kepuasan Pasien dengan Kualitas Pelayanan yang Dirasakan Sebagai Mediasi di UTD PMI Lamongan - Genta Dwi Kurniawan; Vip Paramarta; Feri Kadarusman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of total quality management and therapeutic communication on patient satisfaction with perceived service quality as mediation in the PMI Lamongan Blood Transfusion Unit. The background of this study is based on the phenomenon of fluctuations in patient satisfaction and the imbalance between blood demand and supply. This study uses an explanatory research method with a quantitative approach, where objective, valid, and reliable data is obtained with the aim of discovering, proving, and developing knowledge that can be used to understand, solve, and anticipate problems using Partial Least Square statistical analysis. The study population consists of all patients receiving services at the PMI Lamongan Blood Transfusion Unit, while the sample comprises 100 respondents selected using purposive sampling. Data collection was conducted through a questionnaire using a Likert scale. The results of the study show that there is an influence of Total Quality Management on satisfaction, there is an influence of Therapeutic Communication on patient satisfaction, there is an influence of Service Quality on patient satisfaction, there is an influence of Total Quality Management on patient satisfaction through perceived service quality, and there is no influence of Therapeutic Communication on patient satisfaction through perceived service quality. The research results are expected to provide information to the Blood Transfusion Unit of the Indonesian Red Cross (PMI) in Lamongan District as a reference for improving service quality for patients in an effort to enhance patient satisfaction.